1994
DOI: 10.1029/94gl00640
|View full text |Cite
|
Sign up to set email alerts
|

Detection of creep along the Philippine Fault: First results of geodetic measurements on Leyte Island, central Philippine

Abstract: Geodetic trilateration/GPS measurements were acquired from experiments conducted in 1991 and 1993 in the central part of the Philippine Fault on Leyte island. Displacement vectors deduced from two least squares adjustments indicate a mean slip rate of 26±10 mm/yr at an azimuth of about N130°E. These values are consistent with the tectonic and kinematic data. Our results indicate that the displacements are: (1) almost parallel to the Philippine Fault, and (2) related to creep along the fault, because no moderat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
51
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(57 citation statements)
references
References 7 publications
6
51
0
Order By: Relevance
“…Johnson and Segall (2004) also extended the Savage and Prescott (1978) model to include the localized creep on a linear viscous shear zone within the upper elastic layer. Geographic distribution of the 15 strike-slip faults considered in this study: (1) Alpine, (2) Altyn Tagh, (3) Dead Sea, (4) Elsinore, (5) Fairweather, (6) Garlock, (7) Karakoram, (8) SAF-Mojave, (9) North Anatolian, (10) Owens Valley, (11) Philippine, (12) SAF-Carrizo, (13) SAF-Indio, (14) San Jacinto, and (15) Haiyuan (Sharp, 1967(Sharp, , 1981Savage and Burford, 1973;Plafker et al, 1978;Sieh and Jahns, 1984;Lubetkin and Clark, 1988;Rockwell et al, 1990;Barrier et al, 1991;Lisowski et al, 1991;Merifield et al, 1991;McGill and Sieh, 1993;Beanland and Clark, 1994;Duquesnoy et al, 1994;Petersen and Wesnousky, 1994;Bennett et al, 1996Bennett et al, , 1997Armijo et al, 1999;Beavan et al, 1999;Lasserre et al, 1999;Bendick et al, 2000;Klinger et al, 2000;Reilinger et al, 2000;Argus and Gordon, 2001;Lee et al, 2001;Miller et al, 2001;Niemi et al, 2001;Norris and Cooper, 2001;Banerjee and Bürgmann, 2002;Brown et al, 2002;Hubert-Ferrari et al, 2002;Fletcher and Freymueller, 2003;Meghraoui et al, 2003;Lacassin et al, 2004;…”
Section: Constraining Time-dependent Earthquake-cycle Modelsmentioning
confidence: 99%
“…Johnson and Segall (2004) also extended the Savage and Prescott (1978) model to include the localized creep on a linear viscous shear zone within the upper elastic layer. Geographic distribution of the 15 strike-slip faults considered in this study: (1) Alpine, (2) Altyn Tagh, (3) Dead Sea, (4) Elsinore, (5) Fairweather, (6) Garlock, (7) Karakoram, (8) SAF-Mojave, (9) North Anatolian, (10) Owens Valley, (11) Philippine, (12) SAF-Carrizo, (13) SAF-Indio, (14) San Jacinto, and (15) Haiyuan (Sharp, 1967(Sharp, , 1981Savage and Burford, 1973;Plafker et al, 1978;Sieh and Jahns, 1984;Lubetkin and Clark, 1988;Rockwell et al, 1990;Barrier et al, 1991;Lisowski et al, 1991;Merifield et al, 1991;McGill and Sieh, 1993;Beanland and Clark, 1994;Duquesnoy et al, 1994;Petersen and Wesnousky, 1994;Bennett et al, 1996Bennett et al, , 1997Armijo et al, 1999;Beavan et al, 1999;Lasserre et al, 1999;Bendick et al, 2000;Klinger et al, 2000;Reilinger et al, 2000;Argus and Gordon, 2001;Lee et al, 2001;Miller et al, 2001;Niemi et al, 2001;Norris and Cooper, 2001;Banerjee and Bürgmann, 2002;Brown et al, 2002;Hubert-Ferrari et al, 2002;Fletcher and Freymueller, 2003;Meghraoui et al, 2003;Lacassin et al, 2004;…”
Section: Constraining Time-dependent Earthquake-cycle Modelsmentioning
confidence: 99%
“…Based from this plot, it could be perceived that there is some clustering of large events along the Guinyangan Fault. There were at least one large event and three records of earthquake-related damage in the 17th and 18th (Catane et al, 2000;Duquesnoy et al, 1994) and the location of the 2003 eventon Masbate (Besana et al, 2003) are indicated by light grey and dark grey, respectively. Vertical lines indicate the possible extent of ground rupture using the magnitude estimate from the Wells and Coppersmith (1994) empirical relations.…”
Section: Resultsmentioning
confidence: 99%
“…The northern part of the Central Leyte fault has no record of any major destructive events. The rest of the events (2000), Duquesnoy et al (1994), Catane et al (2000), and Bacolcol (2003), historic slip rates were based on Morante (1974), Besana et al (2003), and Daligdig and Besana (1991), and geologic slip rates were calculated using the regional geologic map of the Philippines (BMG, 1981 recorded on Leyte island are two moderate earthquakes on the southern Central Leyte fault. Interestingly, both of these moderate events occurred with a cluster of foreshocks for at least one week, many of which were perceptible.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Geodetic and geodynamic activities in South-East Asia were concentrated in the past among others on the Sumatra subduction zone (Prawirodirdjo et al, 1997), the Java trench (Tregoning et al, 1994), Irian Jaya and parts of the Philippine fault (Duquesnoy et al, 1994). The GEODYSSEA project, on the contrary, aimed at determining the tectonic motions homogenously for the entire region of South-East Asia.…”
Section: Introductionmentioning
confidence: 99%